Prevalence of Giardiasis among children in childcare centers in Kermanshah, Iran - Faraji, Reza; Ahmadian, Fereshte; Javadi, Gholam Reza; Barshahi, Parisa Mohamadi (International Journal of Research in Medical Sciences, 2017)
Background: Giardia is a common and widespread intestinal protozoan parasite which occurs in of both humans and animals. The aim of this study is determining the prevalence rate of Giardiasis in children, Kermanshah childcare centers (2012). Methods: This cross-sectional study was performed on 632 children (330 were female and 302 were male) with an average of 0-6 years in children, Kermanshah childcare centers (2012). Three stool samples were obtained on three consecutive days and were tested for the detection of trophozoites, and/or cysts, using both direct laboratory methods and Formalin-Ether concentration. Informations were collected by a questionnaire. Results: Of the 632 cases in this study, the prevalence rate of gut parasite infection was 169 (26.74%), so that Giardia lamblia with 13.93%, Entamoeba histolyticawith 3.48%, and Entamoeba coli with 2.53 were the most predominant isolate. The prevalence rate ranged in rural residents (15.67%) was more than urban residents (11.07%). The age group 4-6 years had the highest rate (14.24%) and 0-2 years the lowest (1.74%); boys with 16.29% had a higher rate than girls (10.45%). Parasitic infection was more prevalent in children whose parents had no high education (17.25). The maximum percentage of infections was in August with 5.86%. Conclusion: With attention to the above findings, it seems that in order to decrease, control and prevent of parasitic infection we should have the necessary public education to teachers and parents of children.